Validation of a Methodology for the Detection of Severe Acute Respiratory Syndrome Coronavirus 2 in Saliva by Real-Time Reverse Transcriptase-PCR - Escobar, Daniel F.; Díaz, Pablo; Díaz-Dinamarca, Diego; Puentes, Rodrigo; Alarcón, Pedro; Alarcón, Bárbara; Rodríguez, Iván; Manzo, Ricardo A.; Soto, Daniel A.; Lamperti, Liliana; Díaz, Janepsy; García-Escorza, Heriberto E.; et al. (Frontiers in Public Health, 2021)
In January 2021, the city of Concepción in Chile suffered a second wave of COVID-19, while in early April 2021, all of Chile was facing the same situation. This generated the need to modify and validate a methodology for detecting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in saliva, thereby expanding the capacity and versatility of testing. This study was conducted in February 2021 in the city of Conception in Chile, while this town was under total quarantine. The study participants, mostly symptomatic (87.4%) and not hospitalized, attended care centers because of their health status and not because the researchers asked them to do so. People who came to the health center in Concepción city to perform a test of RT-PCR from a nasopharyngeal swab (NPS) specimen were invited to participate in this study. A total of 131 participants agreed to sign an informed consent and provide saliva and NPS specimens to validate a methodology in terms of sensitivity, specificity, and statistical analysis of the Ct values from RT-PCR. Calculations pertaining to the 127 participants who were ultimately included in the analysis were the following: sensitivity at 94.34% (95% CI: 84.34%-98.82%) and specificity at 98.65% (95% CI: 92.70%-99.97%). The saliva specimen showed a very similar performance to NPS as demonstrated with the diagnostic parameters. This RT-PCR methodology from the saliva specimen is a highly sensitive and specific alternative as compared to the reference methodology, which uses an NPS specimen. This modified and validated methodology is intended for use in the in vitro diagnosis of SARS-CoV-2, which provides health authorities in Chile and local laboratories with a real alternative for RT-PCR from NPS.